Correlating Mass Transfer Coefficients of O2 and N2 in Methanol in a Stirred‐Tank Reactor. Issue 9 (9th August 2022) - Qi, Miao; Dong, Haifeng; Meng, Xianglei; Liu, Guliang; Diao, Yanyan
Abstract: In oxidative esterification of methacrolein to methyl methacrylate, mass transfer of O2 and N2 in methanol is of vital importance for the determination of reaction kinetics and design of industrial units. The mass transfer coefficients k L of O2 and N2 in methanol were determined by the decreasing‐pressure method in a gas‐liquid stirred reactor at temperatures ranging from 298.15 to 333.15 K, pressures ranging from 0.5 to 1.2 MPa, and agitation speeds ranging from 100 to 200 rpm. It could be shown that k L ‐O2 and k L ‐N2 increased with increasing temperature and agitation speed, but did not change significantly with partial pressure. On the basis of the experimental results, theoretical and empirical equations were proposed. This work provides an example of a study on the mass transfer of gases in a liquid. Abstract : Mass transfer of O2 and N2 in MeOH is relevant to production of methyl methacrylate from isobutylene via methacrylic acid. The effects of temperature, pressure, and agitation speed on the mass transfer coefficients k L ‐O2 and k L ‐N2 in MeOH, obtained from experimental O2 /N2 absorption data by the pressure‐drop method, were studied. Equations relating k L to temperature and agitation speed were fitted.